Suicide risk following Emergency Department presentation with self-harm varies by hospital - Siobhán Murphy; Dermot O'Reilly; Emma Ross; Aideen Maguire; Denise O'Hagan (International Journal of Population Data Science, 2023)
Objectives A large proportion of those who die by suicide present to an Emergency Department (ED) with self-harm (SH) in the year before death. This study examines ‘does risk of death following ED presentation with SH vary according to hospital attended?’